Curdione Induces Antiproliferation Effect on Human Uterine Leiomyosarcoma via Targeting IDO1 - Wei, Chao; Li, Donghua; Liu, Yu; Wang, Wenna; Qiu, Tiantian (Frontiers in Oncology, 2021)
Objectives Curdione is one of the active ingredients of a traditional Chinese herbal medicine-Curcuma zedoary and established anti-tumor effects. Uterine leiomyosarcoma (uLMS) is a rare gynecological malignancy, with no standard therapeutic regimen at present. The aim of this study was to explore the potential anti-tumor impact of curdione in uLMS, and elucidate the underlying mechanisms. Methods In vitro functional assays were performed in the SK-UT-1 and SK-LMS-1 cell lines. The in vivo model of uLMS was established by subcutaneously injecting SK-UT-1 cells, and the tumor-bearing mice were intraperitoneally injected with curdione. Tumor weight and volume were measured at specific time points. The biosafety was evaluated by monitoring changes of body weight and the histopathological in the liver and kidney. The expression levels of relevant proteins were analyzed by western blotting and immunohistochemistry. Results Curdione decreased the viability and proliferation of uLMS cells in a concentration and time-dependent manner. In addition, the curdione-treated cells exhibited significantly higher rates of apoptosis and autophagic death. Curdione also decreased the tumor weight and volume in the SK-UT-1 xenograft model compared to the untreated control without affecting the body bodyweight or pathological injury of liver and kidney tissues. At the molecular level, the antitumor effects of curdione were mediated by indoleamine-2, 3-dioxygenase-1 (IDO1). Conclusion Curdione exhibited an anti-uLMS effect in vitro and in vivo, the underlying mechanism involved in IDO1 mediate apoptosis, autophagy, and G2/M phase arrest.